Are landing biomechanics altered in elite athletes with chronic ankle instability? - Lin, J.-Z.; Lin, Y.-A.; Lee, H.-J. (Journal of Sports Science & Medicine, 2019)
Are Landing Biomechanics Altered in Elite Athletes with Chronic Ankle Instability This study analyzed landing strategies used by athletes with chronic ankle instability (CAI) and copers compared to uninjured controls. Thirty participants were asked to perform a single-leg forward jump followed by a single-leg landing. Compared to uninjured controls, those with CAI athletes had significantly greater hip flexion and ankle eversion angles at initial landing, suggesting preference for using hip movements and extra ankle eversion angles to avoid ankle inversion when landing. CAI athletes were also found to have significantly decreased peroneus longus activation and higher ankle inversion velocity were both found during descending phase. And these were potential contributors to cause ankle inversion injury as there were likely many others. Based on these findings, CAI athletes may need to utilize more multi-joint or multi-muscle strategies during landing to maintain stability and prevent re-injury. Key Points